Dimorphic anemia and mental depression as a result of systemic manifestations of generalized aggressive periodontitis: A pioneer case report - Ajay Mahajan; Kanwarjit Asi; Nisha Thakur; Deepali Rasila (Wolters Kluwer Medknow Publications, 2017)
Generalized aggressive periodontitis (GAP) is a rare form of periodontitis resulting in early loss of teeth. Most of the clinical evidence available in literature focuses on the diagnosis and management aspects of GAP. Systemic manifestations of GAP have been reported infrequently. To the best of our knowledge, the present case report is the first-ever evidence providing a possible mechanism and link between GAP, dimorphic anemia, and mental depression suggesting that dimorphic anemia and mental depression are probable systemic manifestations of GAP. A young female reported with her father to the hospital with a complaint of pain in her oral cavity and lack of desire to eat. On thorough examination, GAP with dimorphic anemia and mental depression were diagnosed. Periodontal treatment along with nutritional supplements was prescribed. An improvement was noticed in the patient's condition after a follow-up period of 6 months. Systemic manifestations of GAP should include the diagnoses of dimorphic anemia and mental depression and should be treated accordingly.